Incidence of Intrapartum-Related Events at the Largest Obstetric Hospital in Hanoi, Vietnam: A Retrospective Study - Tina Dempsey; Huong Lien Nguyen; Huong Thu Nguyen; Xuan Anh Bui; Phuong Thi Thu Pham; Toan K. Nguyen; Francesco Cavallin; Daniele Trevisanuto; Susanna Myrnerts Höök; Nicolas Pejovic; Mats Blennow; Linus Olson; et al. (MDPI AG, 2022)
Every year, 2.4 million neonates die during their first month of life and even more suffer permanent injury. The main causes are intrapartum-related events, prematurity, and infection, with sub-Saharan Africa and southern Asia being the worst affected regions. With a focus on intrapartum-related events, we aimed to assess the neonatal demographic characteristics, clinical management, and outcomes among neonates born at the largest obstetric hospital in Hanoi, Vietnam. This was a retrospective cross-sectional study that included all the inborn neonates in November 2019, which was selected as a representative month. A total of 4554 neonates were born during the study period. Of these, 1.0% (n = 44) were stillbirths, 0.15% (n = 7) died in hospital, 0.61% (n = 28) received positive pressure ventilation at birth, and 0.15% (n = 7) were diagnosed with hypoxic ischemic encephalopathy. A total of 581 (13%) neonates were admitted to the neonatal unit, among which the most common diagnoses were prematurity (37%, n = 217) and infection (15%, n = 89). Except for the intrapartum-related events, our findings are consistent with the previously documented data on neonatal morbidity. The intrapartum-related events, however, were surprisingly low in number even in comparison to high-income countries. Research on the current clinical practice at Phu San Hanoi Hospital may bring further clarity to identify the success factors.